UNDERSTANDING OF HUMANISM AT THE CURRENT STAGE OF DEVELOPMENT OF THE UKRAINIAN STATE - N. Bondarenko (Academy of Cognitive and Natural Sciences, 2009)
The article considers new approaches to understanding humanism. Three leading tendencies of realization of educational influence on the person are opened